An improved feature extraction-based colour image matching method using quaternion matrix. (2016) - Zou, Hailin; Liu, Chanjuan; Shen, Qian; Zhou, Shusen; Zang, Mujun
Specific to the problem of feature description for colour image, a novel speeded-up robust features (SURF) descriptor of colour image-based quaternion (CSURF-Q) is proposed in this paper. Firstly, in order to represent the colour information of colour image effectively, the colour information among three channels is expressed by the three imaginary parts of quaternion. This can transform colour image to a pure quaternion matrix, which simplifies the representation process of image colour information. Secondly, the SURF features among three channels of colour image are extracted by using quaternion matrix. Because of the rotation invariance of quaternion norm, feature description vectors are generated as the form of quaternion norm. Finally, comparing CSURF-Q with SURF, FAIR-SURF, CSIFT, SIFT-CCH, colour-SURF and CHSIFT, the experiments prove that, when image appears affine changes, the correct matching of feature point pairs and time complexity are superior.